GMAT Question of the Day - Daily to your Mailbox; hard ones only

 It is currently 07 Dec 2019, 01:36 ### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

#### Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.  # If a + b = x and a - b = y , then 3ab =

Author Message
TAGS:

### Hide Tags

Director  Joined: 29 Nov 2012
Posts: 685
If a + b = x and a - b = y , then 3ab =  [#permalink]

### Show Tags

1
4 00:00

Difficulty:   25% (medium)

Question Stats: 83% (01:47) correct 17% (02:29) wrong based on 135 sessions

### HideShow timer Statistics

If a + b = x and a - b = y , then 3ab =

A. (3x^2 - 3y^2)/4
B. (3y^2 - 3x^2)/4
C. 3x+3y/2
D. 3x - 3y/2
E. 3x^2 - 3y^2/2

can someone explain!
VP  Status: Far, far away!
Joined: 02 Sep 2012
Posts: 1010
Location: Italy
Concentration: Finance, Entrepreneurship
GPA: 3.8
Re: If a + b = x and a - b = y , then 3ab =  [#permalink]

### Show Tags

1
2
$$a=x-b$$
$$a=y+b$$

$$x-b=y+b$$ $$b=\frac{x-y}{2}$$

$$b=x-a$$
$$b=a-y$$

$$x-a=a-y$$ $$a=\frac{x+y}{2}$$

$$3ab=3(\frac{x^2-y^2}{4})$$
A
Director  Joined: 29 Nov 2012
Posts: 685
Re: If a + b = x and a - b = y , then 3ab =  [#permalink]

### Show Tags

Great Explanation! Thanks....
Intern  Status: Currently Preparing the GMAT
Joined: 15 Feb 2013
Posts: 28
Location: United States
GMAT 1: 550 Q47 V23 GPA: 3.7
WE: Analyst (Consulting)
Re: If a + b = x and a - b = y , then 3ab =  [#permalink]

### Show Tags

2
1
Interesting question. Let's try a different approach.

You should recall the following two formulas :

$$(a+b)^2 = a^2 + 2ab + b^2$$
$$(a-b)^2 = a^2 - 2ab + b^2$$

Using what is given in the question stem, we get :

$$a^2 + 2ab + b^2 = (a+b)^2 = x^2$$
$$a^2 - 2ab + b^2 = (a-b)^2 = y^2$$

Substracting the two equations yields : $$4ab = x^2 - y^2$$ meaning that $$ab = \frac{(x^2 - y^2)}{4}$$.

Multiply the result by 3 and we get $$3ab = \frac{3(x^2 - y^2)}{4}$$

Hope that helped Math Expert V
Joined: 02 Sep 2009
Posts: 59587
Re: If a + b = x and a - b = y , then 3ab =  [#permalink]

### Show Tags

1
2
fozzzy wrote:
If a + b = x and a - b = y , then 3ab =

A. (3x^2 - 3y^2)/4
B. (3y^2 - 3x^2)/4
C. 3x+3y/2
D. 3x - 3y/2
E. 3x^2 - 3y^2/2

can someone explain!

Given: $$a + b = x$$ and $$a - b = y$$.

Sum the equations: $$2a=x+y$$.
Subtract: $$2b=x-y$$.

Multiply: $$4ab=x^2-y^2$$ --> multiply by 3/4: $$3ab=\frac{3x^2-3y^2}{4}$$.

_________________
Manager  Status: Working hard to score better on GMAT
Joined: 02 Oct 2012
Posts: 77
Location: Nepal
Concentration: Finance, Entrepreneurship
GPA: 3.83
WE: Accounting (Consulting)
Re: If a + b = x and a - b = y , then 3ab =  [#permalink]

### Show Tags

plugging numbers is quite fast in this case:
Let
a=1
b=2

Then; x= 1+2=> 3 and Y= 1-2=> -1

As our number 3ab= 3*1*2=6

now plug the value of x and y in the answer choices. Option A gives 6 and that is the number we need.

Hence: Ans is A.

Atal Pandit
Manager  S
Joined: 06 Jul 2014
Posts: 87
Location: India
Concentration: Finance, Entrepreneurship
GMAT 1: 660 Q48 V32 Re: If a + b = x and a - b = y , then 3ab =  [#permalink]

### Show Tags

a=x+y/2; b=x-y/2;3ab=3(x^2-y^2/4)= A
Current Student P
Joined: 12 Oct 2015
Posts: 214
GMAT 1: 700 Q47 V39 GPA: 3
WE: Accounting (Accounting)
Re: If a + b = x and a - b = y , then 3ab =  [#permalink]

### Show Tags

Excellent question. saving it in my notebook to try later.
_________________
Winners dont make excuses.

350--> 700

https://gmatclub.com/forum/700-q47-v39-ir-7-awa-246682.html
Senior PS Moderator V
Joined: 26 Feb 2016
Posts: 3300
Location: India
GPA: 3.12
Re: If a + b = x and a - b = y , then 3ab =  [#permalink]

### Show Tags

Plugging values is another method, you can use to solve this one!
Let a=3, b=2, x = 3+2 = 5
Similarly y = 3-2 = 1

We know that 3ab = 3*2*3 = 18

A. (3x^2 - 3y^2)/4 = 3(25) - 3(1)/4 = 75 - 3/4 = 18
B. (3y^2 - 3x^2)/4 = 3(1) - 3(25)/4 = 3 - 75/4 = -18
C. 3x+3y/2 = 3(5) + 3(1)/2 = 9
D. 3x - 3y/2 = 3(5) - 3(1)/2 = 6
E. 3x^2 - 3y^2/2 = 3(25) - 3(1)/2 = 73 - 3/2 = 36

Hence, Option A is the answer.
If you started with evaluating the first choice, it wouldn't take much time to find the answer.
_________________
You've got what it takes, but it will take everything you've got Re: If a + b = x and a - b = y , then 3ab =   [#permalink] 11 Aug 2017, 19:48
Display posts from previous: Sort by

# If a + b = x and a - b = y , then 3ab =  